Optimalisasi Aset Pemerintah Daerah Dengan Analisis Highest And Best Use (Studi Pada Lahan Kosong Di Kelurahan Oebufu Kota Kupang) - Bako, Gladys Marsyanda; Tungga, Cicilia A.; Kiak, Novi T. (Universitas Pahlawan Tuanku Tambusai, 2024)
The aim of this research is to study and apply the Highest and Best Use (HBU) analysis method to assets in the form of empty land that has not been properly utilized which is owned and managed by the Kupang City government. This asset is located in Oebufu Village, Oebobo District, Kupang City, East Nusa Tnggara Province. This research is a quantitative descriptive research. This research collects data through questionnaires, interviews, observation and documentation. This study determines the most optimal type of research land use based on four elements: physical, general, financial, and maximum productivity. The research results show that the highest and best use analysis was carried out from the physical aspect of alternative land uses such as shophouses, multi-purpose buildings and agricultural warehouses and was declared feasible. Based on legal aspects, use as a shophouse and multi-purpose building is permitted, but use as an agricultural warehouse is not permitted. Then, based on the financial aspect, the alternative use of land as a shophouse meets the feasibility, namely an NPV of Rp. 11,107,219,027., IRR of 74% and the highest land value of Rp. 45.235.091530., Multipurpose Building meets the wealth criteria, namely NPV of Rp. 8,350,070,691., IRR of 67% and the highest land value of Rp. 32,168,055,315., The results of the analysis show that the highest and best land value is the alternative use as a shophouse, namely Rp. 59,399,730., per square meter or increasing the land value by 11% compared to the market value of empty land for the research object, which is Rp. 5,221,829., per square meter. So the highest and best use of empty land for optimal results is a shophouse. Then, based on the financial aspect, the alternative use of land as a shophouse meets the feasibility, namely an NPV of Rp. 11,107,219,027., IRR of 74% and the highest land value of Rp. 45.235.091530., Multipurpose Building meets the wealth criteria, namely NPV of Rp. 8,350,070,691., IRR of 67% and the highest land value of Rp. 32,168,055,315., The results of the analysis show that the highest and best land value is the alternative use as a shophouse, namely Rp. 59,399,730., per square meter or increasing the land value by 11% compared to the market value of empty land for the research object, which is Rp. 5,221,829., per square meter. So the highest and best use of empty land for optimal results is a shophouse.